Literature Review: The Impact of Children with Multiple Disabilities in Their Life - Amira Khoirunnisa; Hanifah Ummu Ammaroh; Sarah Febri Cantikaarini; Rafa Libowo; Marcella Cesaria; Citra Ashri Maulidina (Kirana Publisher (KNPub), 2026)
This study reviews previous literature to determine how multiple disabilities affect children. It also examines key components of support services and the education system. Children with various disabilities face complex developmental challenges in cognitive, communication, social, and emotional areas. This study identified four key impacts from 28 scientific articles (2020–2025) using a systematic literature review approach. These four impacts are as follows: “Psychological and Emotional”; “Social and Participation”; “Family and Support Systems,”; and “Education and Services.” The findings suggest that addressing multiple disabilities requires an integrated, personalized, and family-based intervention approach. Furthermore, addressing multiple disabilities requires policies that enable broad social participation and support tailored to children’s complex needs.